Keyboard-less system using EEG Signal - Abd Razak, Najihah (Universiti Teknologi PETRONAS, 2017)
Brain-computer interface is a technology that allow human who suffer from locked-in syndrome to control the computer or other devices to perform the desired task as their communication platform. The aim of this project is to develop a key board-less system using EEG signal for locked-in people to allow them to perform desired simple task such dialing a phone number. A healthy five male students aged between 22-25 years old will participate in the study. Each subject required to think about desired number of 0-9 on the screen that displays randomly